Long noncoding RNA LINC‐PINT regulates laryngeal carcinoma cell stemness and chemoresistance through miR‐425‐5p/PTCH1/SHH axis. Issue 12 (26th May 2019) - Yuan, Zhennan; Xiu, Cheng; Liu, Daming; Zhou, Guangkai; Yang, Hao; Pei, Rong; Ding, Chao; Cui, Xiaowei; Sun, Ji; Song, Kaibin
Abstract: Functional, noncoding RNA of about 200 nucleotides in length are known as long noncoding RNA (lncRNA). Advances in ‐omics have revolutionized the information with respect to the coding and noncoding regions of the genome. Several studies have illustrated the role of lncRNA in cell growth and cancer. Profiling and bioinformatic studies of laryngeal cancer has identified LINC‐PINT as one of the lncRNA. However, the functional aspects of the deregulation have not been studied in laryngeal tumors. In this study, LINC‐PINT expression in normal and tumor tissues were studied. Using a bioinformatic approach, microRNA (miRNA) targets of LINC‐PINT and gene targets of the miRNA were determined. The impact of LINC‐PINT on cell proliferation and chemoresistance was determined. Further through a set of silencing and re‐expression studies phenotype rescue was studied. LINC‐PINT expression was downregulated in laryngeal tumors. LINC‐PINT targeted miR‐425‐5p by three sites. miR‐425‐5p also targeted PTCH1 a protein of the Hedgehog pathway. Downregulation of LINC‐PINT was associated with increased cancer stemness and chemoresistance to cisplatin. Our results indicate a probable role of LINC‐PINT in the pathology of laryngeal tumors. LINC‐PINT re‐expression in laryngeal tumors may be explored for reversion of cancer cell stemness and also for rescue of drug resistance phenotype. Abstract : Our results indicate a probable role of LINC‐PINT in the pathology of laryngeal tumors. LINC‐PINT re‐expression in laryngeal tumors may be explored for reversion of cancer cell stemness and also for rescue of drug resistance phenotype.